Analysis of the reasons for the crisis and insolvency of agricultural enterprises - Kotormán, Annamária (Acta Agraria Debreceniensis, 2009)
The huge insolvency of the enterprise organizations is very adverse for the national economy, the first social and economic task of each country, Hungary as well, should be the maintenance of the efficient and viable organizations. The liquidation of the agricultural organizations has much more economic and social effects. As a result of my researches I declared that most of the time the causes, which led to the liquidation of agricultural organizations, are independent from the organisation and are external. The common feature of external causes are that they are not influenced by the organisations, so they cannot be avoided. So the adaptation to the external causes has huge importance in the battle of avoidance of insolvency.